Unraveling the link between hypertension and depression in older adults: a meta-analysis - Gan, Qingwen; Yu, Ran; Lian, Zerong; Yuan, Yiling; Li, Yuanping; Zheng, Lilan (Frontiers in Public Health, 2023)
Objective To perform a meta-analyses to understand the current status of and risk factors for depression in older adults with hypertension. Methods Eight electronic databases and two clinical trial registries were searched to identify studies examining the incidence of and risk factors for depression among older adults with hypertension. The databases were searched from inception to June 2023. The included studies were evaluated using the Newcastle–Ottawa scale and the evaluation tool recommended by the Agency for Health care Research and Quality. Results A total of 18 studies with 29,694 patients were included. Meta-analysis results showed that the prevalence of depression in older adults with hypertension was 29%. The risk factors for depression among this population included sex [OR value 95% confidence interval 2.24 (1.32, 3.82)], education level [OR 95% CI 1.79 (1.02, 3.14)], residence [OR 95% CI 1.37 (1.24, 1.52)], comorbidities [OR 95% CI 1.79 (1.69, 1.90)], hypertension classification [OR 95% CI 2.81 (1.79, 4.42)], marital status [OR 95% CI 1.50 (1.33, 1.69)], sleep status [OR 95% CI 2.86 (2.21, 3.69)], activity limitation [OR 95% CI 3.42 (2.84, 4.13)], drinking [OR 95% CI 2.25 (1.58, 3.19)], social support [OR 95% CI 3.26 (2.42, 4.41)], living alone [OR 95% CI 1.79 (1.57, 2.04)], stressful events [OR 95% CI 1.62 (1.39, 1.90)], and course of diseases [OR 95% CI 3.23 (2.10, 4.97)]. Conclusion The incidence of depression in older adults with hypertension is high, and there are many risk factors. Clinical health care professionals should intervene early to target the above risk factors to reduce the incidence of depression in older adults with hypertension worldwide. Systematic review registration PROSPERO (york.ac.uk), identifier [CRD42023417106].